Análisis del desarrollo de los sistemas informáticos aplicando la norma ISO 27001 en la empresa Moss Solutions - Murillo García, Alvaro Fabricio (2020)
A computer system is used in the daily management of the productive activity; Its perspective has broadened, evolving over time and from being considered as a tool that reduces bureaucracy and facilitates transactions, it has become considered a strategic weapon that allows the organization to achieve a sustainable competitive advantage. For them, an analysis was carried out in the development of computer systems in the company Moss Solutions to verify if it complies with the security controls, risks of loss of information for them. Several development systems and others that are in production in some companies of the city of Babahoyo, the tools, methodologies and tests they use were analyzed. After having analyzed all these very important points, an evaluation of compliance with the controls was preceded, based on Standard 27001, which is in charge of information security, giving very positive results for the company since it complies with the most control measures. important for the proper protection of information of all its customers.